(untitled) (Journal of Computational Mathematics, 2021)
L. R. Fletcher has pointed out that how to best exploit any freedom of choice in regard to the eigenvalues of a closed-loop system is an unsolved problem for robust pole assignment in control system design. This paper suggests a numerical method to solve this problem. Numerical results show that the method is feasible.